2014
DOI: 10.1371/journal.pone.0087378
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surveillance and Appreciative Inquiry on Puerperal Infections: A Longitudinal Cohort Study in India

Abstract: ObjectiveTo evaluate the effects of an intervention comprising surveillance and an organisational change called Appreciative Inquiry on puerperal infections in hospitals in Gujarat state, India.MethodsThis longitudinal cohort study with a control group was conducted over 16 months between 2010 and 2012. Women who delivered in six hospitals were followed-up. After a five month pre-intervention period, the intervention was introduced in three hospitals. Monthly incidence of puerperal infection was recorded throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 19 publications
0
27
1
Order By: Relevance
“…26 While puerperal sepsis is a known cause of maternal mortality in India, we found only one study that provided estimated incidence of puerperal sepsis in six hospitals in the state of Gujarat. 27 The study reported an incidence of 4%, which is higher than the 0.2% estimated through IndOSS-Assam. 27 A study that reviewed the records of all deliveries in a tertiary hospital in Chandigarh over a period of 15 years (January 1988 to December 2002) found 315 cases of septic abortion among 46 417 deliveries, giving an incidence of 0.7%, which is comparable to that estimated through IndOSS-Assam in the two pilot hospitals, although the case-fatality rate in the Assam hospitals (31%) was higher than that estimated in the Chandigarh hospital (25%).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…26 While puerperal sepsis is a known cause of maternal mortality in India, we found only one study that provided estimated incidence of puerperal sepsis in six hospitals in the state of Gujarat. 27 The study reported an incidence of 4%, which is higher than the 0.2% estimated through IndOSS-Assam. 27 A study that reviewed the records of all deliveries in a tertiary hospital in Chandigarh over a period of 15 years (January 1988 to December 2002) found 315 cases of septic abortion among 46 417 deliveries, giving an incidence of 0.7%, which is comparable to that estimated through IndOSS-Assam in the two pilot hospitals, although the case-fatality rate in the Assam hospitals (31%) was higher than that estimated in the Chandigarh hospital (25%).…”
Section: Discussionmentioning
confidence: 75%
“… 27 The study reported an incidence of 4%, which is higher than the 0.2% estimated through IndOSS-Assam. 27 A study that reviewed the records of all deliveries in a tertiary hospital in Chandigarh over a period of 15 years (January 1988 to December 2002) found 315 cases of septic abortion among 46 417 deliveries, giving an incidence of 0.7%, which is comparable to that estimated through IndOSS-Assam in the two pilot hospitals, although the case-fatality rate in the Assam hospitals (31%) was higher than that estimated in the Chandigarh hospital (25%). 28 A hospital in central India estimated an incidence of 0.06% for uterine rupture over a period of 12 years (1989–2000), with a case-fatality rate of 6%.…”
Section: Discussionmentioning
confidence: 75%
“…Results are from the qualitative study and quantitative findings are reported in another paper ( 19 ). Findings are presented, firstly, as opinions and descriptions of the general situation which included the challenges faced, and secondly, as perceptions of changes which might have occurred as a result of AI.…”
Section: Resultsmentioning
confidence: 99%
“…This qualitative study comprised one component of a wider research project. The second quantitative component monitored post-partum infections in 8,124 women, reported in another paper ( 19 ). The selection of six hospitals was based on the number of deliveries required for the quantitative study including sufficient case load (numbers of deliveries and capacity to deal routinely with obstetric complications), mix of government and private non-profit facilities, willingness to participate, and also other practical considerations like feasibility for follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Primary prevention has become even more important with the emergence of antibiotic resistance, which both limits the effectiveness of antibiotics and necessitates the restriction of their availability. Such restriction in relation to childbirth is acknowledged across the globe, but challenged by recent work in India where almost two‐thirds of deliveries in institutions received antibiotics . Antimicrobial treatment will, of course, still be needed for sepsis cases, but effective prevention will reduce the overall need.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%